2019
DOI: 10.4028/www.scientific.net/msf.944.38
|View full text |Cite
|
Sign up to set email alerts
|

Thermal Deformation Behavior and Critical Conditions of Dynamic Recrystallization of QCr0.8 Alloy

Abstract: In this paper, the flow stresses, the constitutive equation, processing map and the critical conditions of dynamic recrystallization (DRX) of the hot forged QCr0.8 alloy are studied by hot compressive test in the 750-900°C temperature and 0.01-10s-1 strain rate ranges using Gleeble-1500D thermo-mechanical simulator. The compression reduction of thermal compression deformation is 50%. The results show that the thermal deformation temperatures and strain rates have a significant effect on the high temperature de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 14 publications
0
2
0
Order By: Relevance
“…Current research on chromium bronze mainly focuses on unidirectional tensile and compressive responses, while little research has been reported on the deformation behavior of the alloy under cyclic loading. For example, Yang et al. (2019) carried out compression experiments on QCr0.8 alloy and studied the deformation behavior.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Current research on chromium bronze mainly focuses on unidirectional tensile and compressive responses, while little research has been reported on the deformation behavior of the alloy under cyclic loading. For example, Yang et al. (2019) carried out compression experiments on QCr0.8 alloy and studied the deformation behavior.…”
Section: Introductionmentioning
confidence: 99%
“…Current research on chromium bronze mainly focuses on unidirectional tensile and compressive responses, while little research has been reported on the deformation behavior of the alloy under cyclic loading. For example, Yang et al (2019) carried out compression experiments on QCr0.8 alloy and studied the deformation behavior. The thermal deformation activation energy Q of QCr0.8 alloy was obtained based on the hyperbolic sine function model, and a dynamic recrystallization critical strain model was developed.…”
Section: Introductionmentioning
confidence: 99%